Соль земли: [роман] : 16+ / Георгий Марков - Марков Георгий Мокеевич (Сибириада. Собрание сочинений, 2013)
Экземпляры: (20150701) / Инвентарный номер: 38615 / Цена: 202.10 / Сис.шифр: Р2 / Авт.знак: М 27 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6